(p,q)-Analytic functions and a complex (p,q)-binomial formula - Gençtürk İlker (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.5 We introduce the notions of (p,q)-differential for complex discrete functions and (p,q)-complex differential operators in a sense of Pashaev. The (p,q)-analog of the q-binomial formula is presented and the (p,q)-Taylor expansion is constructed for (p,q)-analytic functions. These results provide a generalized framework for (p,q)-calculus, contributing to its applications in mathematical analysis and related fields.